Shear bond strength of orthodontic brackets to enamel under different surface treatment conditions - Matheus Melo Pithon; Márlio Vinícius de Oliveira; Antonio Carlos de Oliveira Ruellas; Ana Maria Bolognese; Fábio Lourenço Romano (University of São Paulo, 2007)
The purpose of the present study was to evaluate the shear bond strength to enamel and the adhesive remnant index (ARI) of both metallic and polycarbonate brackets bonded under different conditions. Ninety bovine permanent mandibular incisors were embedded in acrylic resin using PVC rings as molds and assigned to 6 groups (n=15). In Groups 1 (control) and 3, metallic and polycarbonate orthodontic brackets were, respectively, bonded to the enamel surfaces using Transbond XT composite according to the manufacturer's recommendations. In Groups 2 and 4, both types of brackets were bonded to enamel with Transbond XT composite, but XT primer was replaced by the OrthoPrimer agent. In Groups 5 and 6, the polycarbonate bracket bases were sandblasted with 50-mm aluminum-oxide particle stream and bonded to the enamel surfaces prepared under the same conditions described in Groups 3 and 4, respectively. After bonding, the specimens were stored in distilled water at 37ºC for 24 hours and then submitted to shear bond strength test at a crosshead speed of 0.5 mm/min. The results (MPa) showed no statistically significant difference between Groups 4 and 6 (p>0.05). Likewise, no statistically significant differences (p>0.05) were found among Groups 1, 2, and 5, although their results were significantly lower than those of Groups 4 and 6 (p<0.05). Group 3 had statistically significant lower bond strength than Groups 2, 4, and 6, but no statistically significant differences were found on comparison to Groups 1 and 5. A larger number of fractures at the bracket/composite interface were evidenced by the ARI scores. OrthoPrimer bonding agent yielded higher bond strength in the groups using either conventional or sandblasted polycarbonate brackets, which was not observed in the groups using metallic brackets.